Genetic connectivity of Philippine populations of Siganus fuscescens across multiple spatial scales - Gotanco, Rachel June Ravago (Marine Science Institute, College of Science, University of the Philippines Diliman, 2010)
Dispersal and connectivity between populations shape the distribution of genes, individuals, and species, and have fundamental implications to ecological and evolutionary processes. This dissertation presents patterns of connectivity inferred using genetic approaches, among Philippine populations of a reef-associated fish, the mottled spinefoot siganus fuscescens. A combination of genetic markers (mitochondrial DNA and microsatellites) and analytical methods were emploed to examine gene flow across populations spanning a hierarchy of spatial scales across the Philippine archipelago, o infer historical as well as contemporary processes influencing observed patterns of genetic diversity, variation and gene flow. Phylogeographic analysis of mitochondrial DNA (mtDNA) control region sequences revealed cryptic genetic diversity, with three divergent lineages detected among individuals morphologically identified as S. fuscescens. One lineage was identified as Siganus canaliculatus, while two lineage were monophyletic with S. fuscescens 9clade A and clade B). The timing of linege diversification, demographic history, and patterns of broadscale and regional structure suggest the influence of historical vicariance due to Pleistocence sea-level fluctuations.